KAJIAN PUSTAKA KOKRISTAL GARAM OBAT DAN PENGAMATAN INTERAKSI NATRIUM MEFENAMAT-ISONIKOTINAMID - Ramadhan Sulaiman, Muhammad
Salt-cocrystal is a solid multi-component system formed from salt and its appropriate neutral coformer. The identification of salt-cocrystal is convoluted, hence a reliable method is necessary. This final paper consists of the literature study portion which aims to examine the identification method of salt-cocrystal and the experiment portion which aims to determine whether sodium mefenamate also forms a eutectic mixture with isonicotinamide. According to the literature study, identification of salt-cocrystal is done by proton transfer degree calculation. The instruments capable of correctly identifying this form are Single Crystal X-Ray Diffraction (SCXRD) and Solid-state Nuclear Magnetic Resonance (ssNMR). Mefenamic acid is a nonsteroidal anti-inflammatory agent (NSAID) drug with very low solubility in water, and sodium mefenamate is the sodium salt form with higher solubility in water. Both mefenamic acid and sodium mefenamate form cocrystal with nicotinamide. It has also been reported that mefenamic acid forms a eutectic mixture with isonicotinamide. According to the electrothermal, DSC, FTIR, and PXRD analysis, the interaction of sodium mefenamate-isonicotinamide (1:1) system is a simple eutectic, marked by the melting point which is lower than its constituents, at 66,39°C. The FTIR analysis showed that its spectra are the overlap of the constituents. The PXRD analysis resulted in the diffractograms of the eutectic mixture which in harmony showed that it was the combination of the constituents with no novel peak. Therefore, the sodium mefenamate-isonicotinamide mixture forms a simple eutectic system without forming a novel multi-component system. Future researches may be developed to determine the effect of eutectic interaction on the solubility of sodium mefenamate.